Ski-snow interaction mechanics during the transition from skidding to carving in competitive alpine skiing - Haugen, P.; Reid, R. C.; Gilgien, M.; Kipp, R. C.; Smith, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Skiers manipulate the orientation, edging and pressure of their skis on the snow surface to control their path of motion. Understanding the nature of the ski-snow interaction can thus be important for coaches and skiers for technique and performance optimization. Using a model based on metal cutting theory, Lieu & Mote [1] predicted that the carving process is initiated at the aft-most portions of the ski during the transition from skidding to carving, and that carving is limited to the ski after-body. These are concepts which, if true, have important implications for skiing technique and equipment development yet are poorly understood amongst practitioners. The purpose of this study was to examine how well the Lieu-Mote model predictions correspond to empirical data from a kinematic study of skier technique. METHODS Six male Norwegian national team members completed a slalom race simulation on 2 rhythmical courses set with 10 and 13 m gate separations. Ski 3D position data were reconstructed using 4 panning video cameras for 2 complete turns per athlete per course. The ski position data were then fit with a 15 segment ski model of 14 m sidecut radius. The whole ski attack angle was calculated as the angle between the ski longitudinal axis and the ski center point velocity vector in the plane of the local snow surface [1]. Similarly, the local attack angle at each ski segment was calculated to describe the extent of carving at each point along the ski`s length. Local ski attack angle data were averaged according to whole ski attack angle across all trials and subjects for the turn phase of the turn cycle. RESULTS AND DISCUSSION Some variability in local ski segment attack angle patterns was apparent, likely due to variation in the mechanical and geometrical properties of the skis used by the athletes. In general however, local attack angles were high along the entire ski when whole ski attack angles were greater than about 12º, indicating that skidding processes dominated. Below this level, local attack angles in the aft-most ski segments diminished while those of the fore-body segments remained elevated. Local attack angles of the aft-most segments reached 2-5º as whole ski attack angles approached 8º, indicating the initiation of the transition to carving in good accordance with Lieu and Mote`s [1] predictions. Further decreases in the whole ski attack angle were associated with increasing numbers of tail segments carving along with the reduction of fore-body segment attack angles. The ski reached an advanced carving stage at whole ski attack angles of approximately 2.5º, although fore-body segment attack angles remained slightly elevated indicating that this part of the ski was still machining new snow. CONCLUSION The ski motion characteristics observed in this study are in good accordance with Lieu and Mote ski and snow interaction model. [1] Lieu, D.K. & Mote, C.D. (1983). Skiing Trauma and Safety: Fifth International Symposium, 117-140.